Transcriptome-based protein-protein interaction analysis reveals immune gene network elucidating white body immunity mechanisms in response to LPS stimulation in Amphioctopus fangsiao - Zhengcai Lu; Yancheng Zhao; Tingjin Lv; Xipan Chen; Cuiju Cui; Xiumei Liu; Zan Li; Liyong Wang; Xiaohui Xu; Jianmin Yang (Comparative Immunology Reports)
One of the major challenges in the aquaculture of marine organisms is the susceptibility to pathogens. Immune cells defend bacterial invasion by recognizing pathogen-associated molecular patterns (PAMPs) such as Lipopolysaccharides (LPS) in Gram-negative bacteria. The white body are key organs for immune response and hematopoiesis, and play an important role in understanding the antimicrobial biological response in gold-ringed octopus (Amphioctopus fangsiao). In the present research, transcriptome sequencing and bioinformatics analysis were conducted on A. fangsiao white body tissue after 6 h and 24 h of LPS stimulation. The results showed 2,029 and 73 differentially expressed genes (DEGs) at the 6- and 24-hour time points, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were beneficial in determining immune-related terms and signaling pathways. Subsequently, a protein-protein interaction (PPI) network was constructed and 20 hub genes, such as AKT3, MAPK14, and PIK3CA, were identified. These genes are involved in a variety of signaling pathways, including the Hippo signaling pathway, chemokine signaling pathway, and leukocyte trans endothelial migration. Using qRT-PCR, the accuracy of the 20 hub genes was verified. The present study provides a substantial theoretical foundation for the research on A. fangsiao white body immunity, enhancing the current understanding of cephalopods' innate immunity.